Respuesta :

Answer:

Please check the explanation.

Step-by-step explanation:

Given

  • f(x) = 2x - 1
  • g(x) =  2 - x

a)

f(x) + g(x) = (2x - 1) + (2 - x)

                = 2x -1 + 2 - x

                = x + 1

b)

f(x) - g(x) = (2x - 1) - (2 - x)

              = 2x - 1 - 2 + x

               = 3x - 3

c)

g(-5) - f(-5)

Putting x = -5 in g(x) = 2 - x

g(x) = 2 - x

g(-5) = 2 - (-5) = 2+5 = 7

Putting x = -5 in f(x) = 2x - 1

f(x) = 2x - 1

f(-5) = 2(-5) - 1

       = -10 - 1

        = -11

Thus,

g(-5) - f(-5) = 7 - (-11) = 7+11 = 18

d)

f(x).g(x) = (2x - 1) (2 - x) = -2x² + 5x - 2

e)

f(g(x)) = f(2-x)

          = 2(2-x)-1

          = 4-2x-1

          = 3-2x

ACCESS MORE